AN EMPOWERMENT OF BUMDES ARIH ERSADA EDUTOURISM BASED IN RAYA VILLAGE BERASTAGI DISTRICT KARO DISTRICT - Hamdani Harahap; Yeni Absah; Farid Aulia (Jurnal Scientia, 2023)
The ability to carry out business management is needed to determine the sustainability of agrotourism businesses that are suitable for development by BUMDes Arih Ersada Desa Raya in the future. With good edutourism, BUMDes can create priority strategies for village development through the utilization of BUMDes. The aim of holding training is to increase the capacity of BUMDes administrators to be able to improve and develop the quality of BUMDes administrators to be able to develop edutourism in a sustainable manner. To achieve this goal, the method used in this activity is: Ecotourism Development Socialization and Training. Participatory Organizing, Monitoring and Evaluation. The final achievement of this activity in the form of empowering qualified BUMDes Arih Ersada administrators is certainly a useful input for both the people of Raya Village and other areas. This activity is of course in line with achieving the first priority SDGs (1), namely: no poverty, ensuring that all men and women, especially the poor and vulnerable, have equal rights to economic resources, as well as access to basic services, ownership and control. on land and other forms of ownership, inheritance, natural resources, new technologies and appropriate financial services, including microfinance.